Liberty and poetic licence : new essays on Byron - Beatty, B. G. (Bernard G.); Howe, Tony (Lecturer in English); Robinson, Charles E. (Liverpool English texts and studies, 2008)
This volume runs chronologically from the earliest of Byron's productions, through those of his early maturity, to those of his fullest development. It covers his output in both poetry and prose, and considers many works that have not generally claimed serious critical attention.